Connecting histories in Afghanistan : market relations and state formation on a colonial frontier - Hanifi, Shah Mahmoud (Stanford University Press, 2011)
Most histories of nineteenth-century Afghanistan argue that the country remained immune to the colonialism emanating from British India because, militarily, Afghan defenders were successful in keeping out British imperial invaders. However, despite these military victories, colonial influences still made their way into Afghanistan. Looking closely at commerce in and between Kabul, Peshawar, and Qandahar, this book reveals how local Afghan nomads and Indian bankers responded to state policies on trade. British colonial political emphasis on Kabul had significant commercial consequences both for.